TRADISI KOLOMAN MEMPERKUAT KEARIFAN LOKAL MASYARAKAT ( Sebuah Tradisi Lokal Ritual Keagamaan Masyarakat Desa Blumbungan, Kecamatan Larangan, Kabupaten Pamekasan Madura ) - Mahbub, Syukron (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
There are koloman traditions that are mushrooming in Blumbungan village community such as the Newest Column / Hadrah Sholawatan for the practice of dhikr prayer, the Tahlilan Column, dzikir, and prayer ', the Yasinan Column, read the Qur'an. The Sabellasan column practices the dhikr prayer, the Manakiban column practices the dhikr prayer. The Samman column dhikr prayer ’.Sape column (cow / buffalo and goat) sape traders meeting for economic improvement. The Caca column (speaking) discusses current issues among residents. IHMNU Hajjian Column (Naj Muslimat Hajjah Association). The Khataman column reads the Qur'an. Darusan column, read the Qur'an. The Pangajian column is dzikir and mauidzoh hasanah. The Ustad Column, its members are teachers and religious teachers, practices dhikr and tausiyah. The Friday Friday practice of remembrance. Kolbun (Monthly Column) Amalan Sholawat Nariyah, and Tahlilan. Family column, held every year, which is an arena for family and family descent or known as the association of the children, as well as the various uniqueness of each column. The Koloman tradition as part of the local wealth of the community must be preserved, and strengthened since the impilication of the existence of the Koloman tradition can strengthen the faith and Islamic citizenship, besides that it can create a harmonious life between citizens, far from disunity, can foster morality and harmony, which lately began to be torn and threatened. Community empowerment to continue to develop holds firm awareness, strengthen the tradition of the koloman needs to be supported by a variety of existing elements, this is in order to participate in fighting to maintain the teachings of Islam rahmatan lil alamin which is the Islamic value of the community, because in every activity the koloman is always filled with ritual teachings Islam. Of course, in this case the strategy needs to be strengthened, including approaches and ongoing assistance, if necessary be part of the membership of the colony.